12/15-LOX inhibition or knockout reduces warfarin-associated hemorrhagic transformation following experimental stroke - Liu, Yu (Stroke, 2017)
BACKGROUND AND PURPOSE: For stroke prevention, patients with atrial fibrillation typically receive oral anticoagulation. The commonly used anticoagulant warfarin increases the risk of hemorrhagic transformation (HT) when a stroke occurs, however, and tissue plasminogen activator (tPA) treatment is restricted in these patients. The current study was designed to test the hypothesis that 12/15-LOX inhibition would reduce HT in warfarin-treated mice subjected to experimental stroke. METHODS: Warfarin was dosed orally in drinking water, and International Normalized Ratio (INR) values were determined using a Coaguchek device. C57BL6J mice or 12/15-LOX knockout mice were subjected to transient middle cerebral artery occlusion (MCAO) with 3 hours severe ischemia (Model A); or 2 h ischemia, and tPA infusion (Model B), with or without the 12/15-LOX inhibitor ML351. Hemoglobin was determined in brain homogenates, and hemorrhage areas on the brain surface and in brain sections were measured. 12/15-LOX expression was detected by immunohistochemistry. RESULTS: Warfarin treatment resulted in reproducible increased INR values and significant HT in both models. 12/15-LOX knockout mice suffered less HT following severe ischemia, and ML351 reduced HT in wild-type mice. When normalized to infarct size, ML351 still independently reduced hemorrhage. HT following tPA was similarly reduced by ML351. CONCLUSIONS: In addition to its benefits in infarct size reduction, 12/15-LOX inhibition also may independently reduce HT in warfarin-treated mice. ML351 should be further evaluated as stroke treatment in anticoagulated patients suffering a stroke, either alone or in conjunction with tPA.